2016
DOI: 10.1016/j.ajhg.2016.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in Citron Kinase Cause Recessive Microlissencephaly with Multinucleated Neurons

Abstract: Primary microcephaly is a neurodevelopmental disorder that is caused by a reduction in brain size as a result of defects in the proliferation of neural progenitor cells during development. Mutations in genes encoding proteins that localize to the mitotic spindle and centrosomes have been implicated in the pathogenicity of primary microcephaly. In contrast, the contractile ring and midbody required for cytokinesis, the final stage of mitosis, have not previously been implicated by human genetics in the molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
57
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 37 publications
1
57
1
Order By: Relevance
“…Indeed, four recent studies have reported that mutations in CIT are responsible for some cases of primary microcephaly in humans (Basit et al, 2016;Harding et al, 2016;Li et al, 2016;Shaheen et al, 2016), thereby, further supporting this hypothesis and, for the first time, linking CIT-K to human disease. In both rodents and humans, the defects in CNS development were associated with failure of cytokinesis and severe apoptosis.…”
Section: Cit-k and Diseasementioning
confidence: 70%
See 4 more Smart Citations
“…Indeed, four recent studies have reported that mutations in CIT are responsible for some cases of primary microcephaly in humans (Basit et al, 2016;Harding et al, 2016;Li et al, 2016;Shaheen et al, 2016), thereby, further supporting this hypothesis and, for the first time, linking CIT-K to human disease. In both rodents and humans, the defects in CNS development were associated with failure of cytokinesis and severe apoptosis.…”
Section: Cit-k and Diseasementioning
confidence: 70%
“…The CIT-K-binding partner ASPM is one of the most frequently mutated genes in autosomal-recessive human microcephaly and one of the main determinants of human brain size (Nicholas et al, 2009), suggesting that a common cellular mechanism underlies the cause of primary microcephaly. The presence of multinucleated neurons in patients carrying CIT mutations (Harding et al, 2016;Li et al, 2016) and the established roles for both CIT-K and ASPM in cytokinesis (Higgins et al, 2010;Paramasivam et al, 2007) suggest that cytokinesis failure and, consequently, apoptosis is one such possible mechanism. However, as both proteins also cooperate in spindle orientation , defects during this step of mitosis cannot be discounted as a possible cause.…”
Section: Cit-k and Diseasementioning
confidence: 99%
See 3 more Smart Citations